Carbohydrate supplementation and perceived exertion during resistance exercise - Utter, A. C.; Kang, J.; Nieman, D. C.; Brown, V. A.; Dumke, C. L.; McAnulty, S. R.; McAnulty, L. S. (The Journal of Strength and Conditioning Research, 2005)
The purpose of the present study was to investigate the relationship between carbohydrate energy substrate and the perception of exertion during resistance exercise. Thirty strength-trained subjects were randomized to a carbohydrate group (C) or a placebo group (P), and lifted weights for 2 hours (4 sets; 10 repetitions maximum; 10 exercises; 2-3-minute rest intervals). Subjects ingested 10 ml·kg?1·h?1 of 6% carbohydrate or placebo beverages during the resistance-training bout. The 15-category Borg Perceived Exertion Scale was used to assess overall body (RPE-O) and active muscle (RPE-AM) perceived exertion after completion of the last repetition in each set for each exercise. No significant differences were found between the C and P groups for either RPE-O or RPE-AM, with the exception of RPE-O for the upright row and back squat (p < 0.05). Carbohydrate supplementation exerted no attenuating effect on ratings of perceived exertion (RPE) during resistance training.